New Relational Processes in Social Services - Boccacin, Lucia (Italian Sociological Review, 2017)
The paper proposes a comparison between current thought and on-going research concerning social partnerships, social co-production and governance. The term partnership refers to a structural configuration characterized by the co-presence of state, market and third sector and by collaborative social action that seeks to achieve project goals. The concept of co-production concerns the participation of individual initiatives among the general public, the goal of which is to benefit the city itself and the contribution of the subject to the production process of services, through participation in voluntary organizations and networks of relationships. The function of governance often affects the role that third sector organizations can play in policy planning. The consideration these three concepts has recently begun to be explored in surveys and qualitative studies conducted in Italy and looks to be useful in promoting understanding of emerging configurations of the third sector in the field of human services.